The Challenges for Implementation of Policies Causing A Delay in Mass Immunization Against Covid-19: A Cross Sectional Qualitative Study - Areeb Amjad, Asfar Anwar, Shujaat Ali, Farah Waseem, Hadia Khan, Mariyah Hidayat (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To investigate the policy barriers leading to hindrance in mass immunization of Covid-19 in Pakistan. Study design: A cross-sectional qualitative study was Duration of study: study was conducted from October 2021 to April 2022 Place of study: was conducted on 106 individuals at 4 vaccination centers of Lahore, including Expo center, Pakistan Kidney and Liver Institute and research center (PKLI), Lahore Developmental Authority (LDA) sports complex, Railway dispensary Model Town. Methodology: It covered interviews, focus group discussions and filling in of semi- structured questionnaires from the general public visiting the vaccination center. Individual interviews of hospital administrators and focused group interviews of general public visiting various hospitals of Lahore, including Jinnah Hospital, Services hospital, Lady Wallington hospital and University of Lahore Teaching Hospital were also included in this study. The data obtained was transcribed and analyzed by using SPSS software version 21. The theme we chose was Politically Informed Views and the subthemes were common hurdles, common myths, different vaccine brands, lack of awareness and conspiracy theories. Results: The results were significant (P<0.05) with the levels of different variables as: Common hurdles 41%; Common myth 25%; Religious Aspects 17%; Different brands 7% ; Lack of awareness 10% respectively. Each variable showed a remarkable difference from considered standard SOPs. Conclusion: To increase the vaccination drive, proper implementation of the already established government policies, with better surveillance and monitoring of the vaccine centers is required. Awareness among the general population should also be increased to debunk myths and motivate them. Keywords: COVID-19, vaccination, immunization, Sino-pharm, Sino-vac.